Cultures of legality judicialization and political activism in Latin America - Couso, Javier, 1964-; Huneeus, Alexandra, 1967-; Sieder, Rachel; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2010)
"This volume explores the changing legal ideas and practices that accompany, cause, and are a consequence of the judicialization of politics in Latin America"--Provided by publisher.
"Ideas about law are undergoing dramatic change in Latin America. The consolidation of democracy as the predominant form of government and the proliferation of transnational legal instruments have ushered in an era of new legal conceptions and practices. Law has become a core focus of political movements and policy-making. This volume explores the changing legal ideas and practices that accompany, cause, and are a consequence of the judicialization of politics in Latin America. It is the product of a three-year international research effort, sponsored by the Law and Society Association, the Latin American Studies Association, and the Ford Foundation, that gathered leading and emerging scholars of Latin American courts from across disciplines and across continents"--Provided by publisher.
Cultures of legality : judicialization and political activism in contemporary Latin America / Alexandra Huneeus, Javier Couso, and Rachel Sieder -- Legal language and social change during Colombia's economic crisis / Pablo Rueda -- How courts work : culture, institutions, and the Brazilian Supremo tribunal federal / Diana Kapiszewski -- More power, more rights? The Supreme Court and society in Mexico / Karina Ansolabehere -- Rejecting the Inter-American Court : judicialization, National Courts,and regional human rights / Alexandra Huneeus -- The transformation of constitutional discourse and the judicialization of politics in Latin America / Javier Couso -- Legal cultures in the (un)rule of law : indigenous rights and juridification in post-conflict Guatemala / Rachel Sieder -- Political activism and the practice of law in Venezuela / Manuel A. Gomez -- The Mapuche people's battle for land : litigation as a strategy to defend indigenous land rights / Anne Skj'vestad -- Judicialization in Argentina : legal culture, or opportunities and support structures? / Catalina Smulovitz -- Novel appropriations of the law in the pursuit of political and social change in Latin America / Pilar Domingo.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Law -- Latin America -- Philosophy; Justice, Administration of -- Latin America; Courts -- Latin America; Electronic books